Structural Strengthening of Insufficiently Designed Reinforced Concrete T-Beams using CFRP Composites - Hasan Ehssan Alobaidi; Alaa Hussein Al-Zuhairi (Salehan Institute of Higher Education, 2023)
This study aims to compare the response of reinforced concrete (RC) T-beams strengthened with carbon fibre-reinforced polymer (CFRP) composite with that of non-strengthened control beams when subjected to monotonic two-point loading until failure for flexural once and shear again. The experimental programme tested eight RC T-beams, which included two reference beams without strengthening and six strengthened beams. The eight beams were divided into two main groups according to strengthening (flexural and shear). Experimental analysis was performed to study the effect of the CFRP laminate width in the flexural group and the spacing of CFRP U-wrap sheets in the shear group on the ultimate load capacity, load-strain relationship, and load-deflection relationship. Results show that increasing the width of the CFRP laminate in the flexural group improves the ultimate strengths to approximately 9.5%, 35%, and 41% for beams with CFRP laminate widths of 50, 100, and 150 mm, respectively, compared with the reference non-strengthened beam. The stiffness of the beams increases in direct proportion to the width of the CFRP laminate. In the meantime, decreasing the spacing of the CFRP laminate in the shear group increases the ultimate strengths to approximately 13.2%, 17.7%, and 23.5% for beams with CFRP U-wrap sheet spacings of 166, 125, and 100 mm, respectively, compared with the reference non-strengthened beam. Therefore, the spacing of the CFRP sheet is inversely proportional to the stiffness of the beam.Â Doi: 10.28991/CEJ-2023-09-08-05 Full Text: PDF